'The role of accommodative function in myopic development: A review.'. (19th May 2022) - Prousali, Efthymia; Haidich, Anna-Bettina; Tzamalis, Argyrios; Ziakas, Nikolaos; Mataftsi, Asimina
ABSTRACT: Involvement of the accommodative mechanism in myopia progression has been hypothesised and investigated over the past years. The initial stimulus for accommodation is derived from near work, in an attempt of the eye to obtain a clear image. When there is a lag in accommodative response, the resulting blurred retinal image is believed to precipitate axial elongation and lead to myopia development. Given the myopia crisis across the globe, the phenomenal connection between the accommodative mechanism and myopia development warrants further investigation. The dynamic accommodative functions implicated in binocular vision evaluation include the accommodative accuracy, amplitude and facility. Association of these accommodative parameters to current treatment options for myopia control is of great clinical interest. Effective treatments, including orthokeratology, multifocal lenses and atropine eyedrops, appear to induce changes in the dynamic accommodative response. This review aims at investigating the clinical role of accommodative function in myopia development and at exploring its use as a promising myopia-monitoring tool.